The impact of network capabilities and entrepreneurial orientation on university spin-off performance - Walter, Achim; Auer, Michael; Ritter, Thomas (Journal of Business Venturing, 2006)
Drawing on a database of 149 university spin-offs, we investigated the impact of network capability (NC), defined as a firm's ability to develop and utilize inter-organizational relationships, and entrepreneurial orientation (EO) on organizational performance. Not only do the results suggest that a spin-off's performance is positively influenced by its NC, but the findings also indicate that a spin-off's EO fosters competitive advantages. Although no direct relationship is apparent between EO and sales growth, sales per employee, or profit attainment, moderated hierarchical regression analyses reveal that NC strengthens the relationship between EO and spin-off performance. In sum, our research shows that a spin-off's organizational propensities and processes that enhance innovation, constructive risk taking, and proactiveness in dealing with competitors per se do not enhance growth and secure long-term survival. However, we found that NC moderates the relationship between EO and organizational performance.